The transcriptional characteristics of NADC34-like PRRSV in porcine alveolar macrophages - Peixin Wang; Xin Ma; Riteng Zhang; Yongxin Zhao; Ruochen Hu; Chen Luo; Basit Zeshan; Zengqi Yang; Li Qiu; Juan Wang; Haijin Liu; Yefei Zhou; et al. (Lausanne : Frontiers Research Foundation, 2022)
The widespread and endemic circulation of porcine reproductive and respiratory syndrome virus (PRRSV) cause persistent financial losses to the swine industry worldwide. In 2017, NADC34-like PRRSV-2 emerged in northeastern China and spread rapidly. The dynamics analysis of immune perturbations associated with novel PRRSV lineage is still incomplete. This study performed a time-course transcriptome sequencing of NADC34-like PRRSV strain YC-2020-infected porcine alveolar macrophages (PAMs) and compared them with JXA1-infected PAMs. The results illustrated dramatic changes in the host’s differentially expressed genes (DEGs) presented at different timepoints after PRRSV infection, and the expression profile of YC-2020 group is distinct from that of JXA1 group. Functional enrichment analysis showed that the expression of many inflammatory cytokines was up-regulated following YC-2020 infection but at a significantly lower magnitude than JXA1 group, in line with the trends for most interferon-stimulated genes (ISGs) and their regulators. Meanwhile, numerous components of histocompatibility complex (MHC) class II and phagosome presented a stronger transcription suppression after the YC-2020 infection. All results imply that YC-2020 may induce milder inflammatory responses, weaker antiviral processes, and more severe disturbance of antigen processing and presentation compared with HP-PRRSV. Additionally, LAPTM4A, GLMP, and LITAF, which were selected from weighted gene co-expression network analysis (WGCNA), could significantly inhibit PRRSV proliferation. This study provides fundamental data for understanding the biological characteristics of NADC34-like PRRSV and new insights into PRRSV evolution and prevention.